School labors of memory in Argentina. Interpretations and questions about teaching history arised from Spain - Rolland, Jorge (Historia y Memoria de la Educación, 2023)
The broad and complex evolution shown by Argentinean schools dealing with recent history may serve as a reference point for the ongoing discussion about the didactics of the Spanish Civil War and the Franco Era, as well as of political violence in History, taking caution, of course, with certain ethical considerations. Here I propose a particular and introductory understanding of that case, based on the history of education's transnational approach and three contrasting aspects in relation to the Spanish one: the broad coverage; exchanges between past and present; and the forging of a certain consensus. By means of a diachronic and a synchronic review, including some general results of my own research- ethnographically oriented and carried out in the city of La Plata - we will notice that these labors of memory reveal (i) the interrelation between several temporalities and dimensions —cognitive, ethic, and political—, (ii) the intertwining with specific webs of relations —institutional and social—, (iii) the perseverance of school culture and the disciplinary code of teaching history, and (iv) the links with social struggles and power.